¿Una crítica de Apolonio Díscolo a la Téchne grammatiké? Enfoques en torno de la noción de diáthesis en la gramática griega antigua - Mársico, Claudia T. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2006)
The question of the authenticity of the Téchne grammatiké, attributed by the tradition to Dionisius Thrax, is a persistent problem for the history of linguistic ideas. Their relevance goes beyond the identity of the author. Indeed, it is related to the plausibility that the theoretical positions adopted in the TG were sustained in an early date. Based on the study of diáthesis in the TG and in Apolonius Dyscolus’ Syntax, we will sustain that the critic involved in this last treatment supposes that one attributed to Dionisius. This could be an indication of the antiquity of the doctrine presented in the TG.
Keywords: Grammar; Linguistics; Diáthesis; Verb; Voice